Hospitalizations, Costs, and Outcomes Associated with Heroin and Prescription Opioid Overdoses in the United States 2001–2012 - Hsu, Douglas J. (Addiction, 2017)
BACKGROUND AND AIMS: The full burden of the opioid epidemic on U.S. hospitals has not been described. We aimed to estimate how heroin (HOD) and prescription opioid (POD) overdose-associated admissions, costs, outcomes, and patient characteristics have changed from 2001 – 2012. DESIGN: Retrospective cohort study of hospital admissions from the National Inpatient Sample. SETTING: United States of America. PARTICIPANTS: Hospital admissions in patients 18 years of age or older admitted with a diagnosis of HOD or POD. The NIS sample included 94,492,438 admissions from 2001 – 2012. The final unweighted study sample included 138,610 admissions (POD – 122,147 and HOD – 16,463). MEASUREMENTS: Primary outcomes were rates of admissions per 100,000 persons using U.S. Census Bureau annual estimates. Other outcomes included inpatient mortality, hospital length-of-stay, cumulative and mean hospital costs, and patient demographics. All analyses were weighted to provide national estimates. FINDINGS: Between 2001 and 2012, an estimated 663,715 POD and HOD admissions occurred nationwide. HOD admissions increased 0.11 per 100,000 persons per year (95% CI 0.04, 0.17), while POD admissions increased 1.25 per 100,000 persons per year (95% CI 1.15, 1.34). Total inpatient costs increased by $4.1 million dollars per year (95% CI 2.7, 5.5) for HOD admissions and by $46.0 million dollars per year (95% CI 43.1, 48.9) for POD admissions, with an associated increase in hospitalization costs to over $700 million annually. The adjusted odds of death in the POD group declined modestly per year (OR 0.98, 95% CI 0.97, 0.99), with no difference in HOD mortality or length-of-stay. Patients with POD were older, more likely to be female, and more likely to be white compared with HOD patients. CONCLUSIONS: Rates and costs of heroin and prescription opioid overdose related admissions in the U.S. increased substantially from 2001 to 2012. The rapid and ongoing rise in both numbers of hospitalizations and their costs suggests that the burden of POD may threaten the infrastructure and finances of U.S. hospitals.